Experiences of patient advocacy among nurses working in a resource constrained emergency department in Ghana. (March 2023) - Adjei, Mabel Dorothy; Diji, Abigail Kusi-Amponsah; Oduro, Evans; Bam, Victoria Bubunyo; Dzomeku, Veronica Millicent; Budu, Isaac Hayford; Lomotey, Alberta Yemotsoo; Sakyi, Richard; Kyerew, Abena Abebrese
Highlights: Emergency nurses are demotivated to advocate when advocacy fails. Educational background prepared emergency nurses for advocacy role. There is a need for health policy to guide the process of advocacy. Abstract: Background: Patient advocacy at the emergency department is stressful and cumbersome as a result of the increasing patient-to-nurse ratio and high patient turnovers. It is also unclear what patient advocacy entails and the experiences of patient advocacy in a resource-constrained emergency department. This is significant because advocacy underpins the care provided in the emergency department. Aim: The primary aim of this study is to explore the experiences and underpinning factors that influence patient advocacy among nurses working in a resource constrained emergency department. Methods: A descriptive qualitative study was conducted among 15 purposively sampled ED nurses working at a resource-constrained secondary-level hospital facility. Study participants were individually interviewed via a recorded telephone conversation, after which the interviews were transcribed verbatim and inductively analyzed using the content analysis approach. The study participants described patient advocacy, situations in which they advocated for patients, the factors that motivated them and the challenges they encountered practicing patient advocacy. Results: Three major themes generated from the study included: "stories of advocacy", "motivating" factors and "challenging" factors. ED nurses understood patient advocacy and also advocated for patients in various instances. There were factors such as personal upbringing, professional training and religious training that motivated them and they were challenged by negative inter-professional experiences, patient and relatives' attitudes and healthcare system factors. Conclusion: Participants understood patient advocacy and incorporated it into daily nursing care. Unsuccessful advocacy causes disappointment and frustrations. There were no documented guidelines on patient advocacy.